2017
DOI: 10.1088/1674-1056/26/4/044202
|View full text |Cite
|
Sign up to set email alerts
|

Tunable second harmonic generation from a Kerr-lens mode-locked Yb:YCa 4 O(BO 3 ) 3 femtosecond laser

Abstract: We experimentally demonstrated a diode-pumped Kerr-lens mode-locked femtosecond (fs) laser with a self-frequency doubling Yb:YCa 4 O(BO 3 ) 3 crystal. Sub-40 fs laser pulses were directly generated from the oscillator without extracavity compression. The central wavelength was tunable from 1039 nm to 1049 nm with a typical bandwidth of 35 nm and an average output power of 53 mW. For the first time, a self-frequency doubled second harmonic green laser with tunable range from 519 nm to 525 nm was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…[6,7] These features make Yb 3+ -doped materials suitable for use as gain media for ultrashort and high-power lasers. [8][9][10][11] Prior studies have indicated that rare-earth ion-doped calcium fluoride (such as CaF 2 , SrF 2 ) materials are promising for the development of ultrashort pulsed solid-state lasers. [12][13][14][15][16][17][18] Among these materials, Yb 3+ -doped fluoride-based materials have attracted great attention because of the excellent properties such as broad range of transmittance, low phonon energy, high thermal conductivity, and low refractive index.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] These features make Yb 3+ -doped materials suitable for use as gain media for ultrashort and high-power lasers. [8][9][10][11] Prior studies have indicated that rare-earth ion-doped calcium fluoride (such as CaF 2 , SrF 2 ) materials are promising for the development of ultrashort pulsed solid-state lasers. [12][13][14][15][16][17][18] Among these materials, Yb 3+ -doped fluoride-based materials have attracted great attention because of the excellent properties such as broad range of transmittance, low phonon energy, high thermal conductivity, and low refractive index.…”
Section: Introductionmentioning
confidence: 99%